TOPK promotes immune suppression in kidney renal clear cell carcinoma and emerges as a prognostic and therapeutic target - Zeyuan Zheng; Renhui Xiong; Xiuyuan Sui; Liyan Li; Huimin Sun; Chen Shao (BMC Cancer)
Abstract The T-LAK cell-originated protein kinase (TOPK) has been associated with poor prognosis in various cancers, yet its specific role in kidney renal clear cell carcinoma (KIRC) remains unclear. In this study, we conducted a comprehensive investigation of TOPK expression and its association with immune infiltration in KIRC by integrating bioinformatics, in vitro, and in vivo approaches. We found that TOPK is significantly overexpressed in KIRC and serves as an independent prognostic marker correlated with aberrant promoter methylation. High TOPK expression was associated with reduced infiltration of cytotoxic immune cells and increased immune checkpoint expression, indicating its potential role in shaping an immunosuppressive tumor microenvironment (TME). Functional enrichment analysis further linked TOPK to key inflammatory signaling pathways, including NOTCH1, TNF-α, and TGF-β. In vivo experiments using TOPK-deficient tumor models in immunocompetent mice supported its role in modulating tumor-associated inflammation.While these experiments were based on a non-renal tumor model, the findings nonetheless provide meaningful insights into the immunoregulatory function of TOPK in vivo. Collectively, our results identify TOPK as a promising prognostic biomarker and immunotherapeutic target in KIRC, and offer novel perspectives on its involvement in immune evasion mechanisms.